2019
DOI: 10.1371/journal.pone.0213729
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and oral sex practice among dental clinic attendees

Abstract: Tobacco use and oral sex (OS) are important risk factors for oral and oropharyngeal Human papillomavirus (HPV) infection. Little is known about the prevalence of OS practice in South Africa. This study aimed to determine the prevalence of OS practice and tobacco use in a South African patient population. This cross-sectional study used a structured questionnaire to collect socio-demographic characteristics, tobacco use, betel nut use and OS practice data from consenting adults (≥18 years; n = 850). Oral sex pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(52 reference statements)
0
4
2
Order By: Relevance
“…is is much higher than a previous report published from the same area, which revealed that 22.4% of participants practiced oral sex [15]. In this current study, no link between the practice of oral sex and HPV presence could be demonstrated following analysis of the data in part because of the extraordinary low prevalence of HPV detected.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…is is much higher than a previous report published from the same area, which revealed that 22.4% of participants practiced oral sex [15]. In this current study, no link between the practice of oral sex and HPV presence could be demonstrated following analysis of the data in part because of the extraordinary low prevalence of HPV detected.…”
Section: Discussioncontrasting
confidence: 87%
“…The proportion of participants who reported to have ever practiced oral sex were 46.3% for the dental clinic attendees and 50.0% for the patients attending the HIV management clinic (47.5% combined). This is much higher than a previous report published from the same area, which revealed that 22.4% of participants practiced oral sex [ 15 ]. In this current study, no link between the practice of oral sex and HPV presence could be demonstrated following analysis of the data in part because of the extraordinary low prevalence of HPV detected.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Although oral sex was not practised by the majority of participants, it was practised by those who were positive with HR-HPV types. However, a recent study on oral sexual practices of dental clinic attendees from the general population in same catchment area determined that 18–35 years old tended to practice more oral sex, and 21.8% of the total cohort confirmed to practice oral sex [26] . Males reported a significantly higher prevalence of oral sex practice than the females, and at 32% compares favourably to that reported by Davidson et al [25] and also of the current oral sex practice reported in this study of 28.6% (n = 57).…”
Section: Discussionmentioning
confidence: 96%